Conceptual and mythological world picture of traditional Kazakh music (Eurasian Journal of Philology Science and Education, 2015)
World pictures are extremely diverse, it’s always a kind of a world vision, its semantic construction takes place in accordance with a certain logic of the world outlook. Comparing different cultures and their world vision we can reveal specific national features of world perception. Shamanism as ancient religion is based on faith in the existence of spirits and special mediator baqsi shaman, who mastered the whole magical practice, harking back to the era of primitive syncretism. The secret of the effect of baqsi’s music is in a special nature of kobyz sounds, mysterious lowtone of which can cause the corresponding hypnotizing mood, giving the melody a “mystical”, “underworld nature”. The relatedness of the ancient forms and meanings enclosed in anthropomorphous structure of kobyz construction, conceals a hidden, inexplicable energy and is of a sacral character. Folk etymology is called “the etymological magic, which merges with the other, non-linguistic (ritual, mythological) types of magic”. We use this concept in relation to etymological versions of baqsi and kobyz concepts, storing darkened semantic secrets of the peculiarities of Kazakhnation’s world picture obliterated in language.
Keywords: concept of baqsi; kobyz; sacral rite of baqsi; mythological mind; legends and myths